2011
DOI: 10.1177/0218492311410874
|View full text |Cite
|
Sign up to set email alerts
|

Streptokinase for malignant pleural effusions: a randomized controlled study

Abstract: Effective palliative treatment in malignant pleural effusion can only be carried out when the lung is fully expanded after drainage of effusion. We investigated the efficacy of intrapleural fibrinolytics for lysing fibrin deposits and improving lung reexpansion in patients with malignant pleural effusion. We randomly allocated 47 patients with malignant pleural effusion into 2 groups: a fibrinolytic group of 24 were given 3 cycles of 250,000 U intrapleural streptokinase; the control group of 23 received pleura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 14 publications
3
23
0
2
Order By: Relevance
“…Two small trials of intrapleural instillation of streptokinase in patients with MPE previously found no significant difference in fluid recurrence rates after pleurodesis even though pleural fluid drainage and lung re-expansion improved. 91,92 Similar findings have been reported in the TIME-3 randomized trial (n ¼ 71) that used intrapleural urokinase (100,000 IU, three doses 12 hourly) followed by talc pleurodesis in patients with a septated, nondraining malignant effusion. 93 Urokinase instillation reduced the effusion size on chest radiograph but did not improve dyspnea or pleurodesis failure rates.…”
Section: Role Of Fibrinolytic Therapy In Loculated Effusionsupporting
confidence: 67%
“…Two small trials of intrapleural instillation of streptokinase in patients with MPE previously found no significant difference in fluid recurrence rates after pleurodesis even though pleural fluid drainage and lung re-expansion improved. 91,92 Similar findings have been reported in the TIME-3 randomized trial (n ¼ 71) that used intrapleural urokinase (100,000 IU, three doses 12 hourly) followed by talc pleurodesis in patients with a septated, nondraining malignant effusion. 93 Urokinase instillation reduced the effusion size on chest radiograph but did not improve dyspnea or pleurodesis failure rates.…”
Section: Role Of Fibrinolytic Therapy In Loculated Effusionsupporting
confidence: 67%
“…Four controlled studies, three of which were randomised, investigated the role of intra-pleural fibrinolysis for the treatment of loculated MPE [89,[111][112][113]. The first, which used a historical control group, prospectively evaluated 36 patients with symptomatic loculated MPE after drainage with an 8F catheter who were unsuitable for surgery [89].…”
Section: Question 3: How Should Septated and Loculated Malignant Pleumentioning
confidence: 99%
“…The second study randomised 47 patients with symptomatic MPE to receive intra-pleural streptokinase (250 000 IU twice daily for three doses) or pleural drainage only [111]. No information was provided regarding the existence of pleural adhesions.…”
Section: Question 3: How Should Septated and Loculated Malignant Pleumentioning
confidence: 99%
“…Randomized, controlled evaluation of intrapleural streptokinase for MPE revealed lung re-expansion for a greater number of patients (96 % versus 75 %) and increased subsequent success with doxycycline pleurodesis (75 % versus 56 %) [9]. An indwelling pleural catheter can also be inserted with ultrasound guidance into the dominant loculated space for symptom relief.…”
Section: Loculated Malignant Effusionmentioning
confidence: 99%